Hemodynamic tolerability and efficacy of hemodialysis modalities in critically ill patients - Varun Kumar Bandi; Manikantan Shekar; Ramprasad Elumalai; Jayakumar Matcha (SpringerOpen, 2024)
Abstract Introduction Acute kidney injury (AKI) is frequently seen in critically ill patients and is associated with high mortality and morbidity. However, the optimal dialysis modality in such patients remains controversial. We examined the hemodynamic tolerability of hemodialysis modalities in critically ill individuals with AKI. Methodology Critically ill patients with AKI who underwent Continuous Renal Replacement Therapy (CRRT), Sustained Low-Efficiency Diafiltration (SLEDD-f), or Sustained Low-Efficiency Dialysis (SLED) dialysis were included in the study. In-hospital mortality, number of dialysis sessions, number of sessions terminated pre-maturely, change in blood pressure during dialysis, and hemodynamic instability during dialysis sessions were noted. Results A total of 264 patients were included, of which 78 received Continuous Renal Replacement Therapy (CRRT), 62 received Sustained Low-Efficiency Diafiltration (SLEDD-f), and 124 received Sustained Low-Efficiency Dialysis (SLED), with a total of 682 sessions among 264 patients. The commonest cause for AKI was septic shock (32.6%, n=43). All CRRT and SLEDD-f sessions were delivered without anticoagulation, and SLED was delivered without anticoagulation in 88.7% of sessions. There was a significant decrease in mean arterial pressure in CRRT compared to other modalities, with higher mortality. However, patients undergoing CRRT were more sicker. There was no significant difference between SLEDD-f and SLED in terms of outcomes. Conclusion SLEDD-f and SLED have good hemodynamic tolerability compared to CRRT. There was no significant difference in hemodynamic disturbances between SLEDD-f and SLED despite a higher proportion of patients on SLEDD-f being more critical.